Analyzing rates of seriously delinquent mortgages in Asian census tracts in the United States - Anacker, Katrin B. (2019)
Although race and ethnicity have been analyzed and discussed in the context of the national foreclosure crisis, there has been little work on neighborhoods in which different Asian subgroups reside, which is surprising given the relatively large demographic, economic, and social differences. Based on NSP 3 data, provided by the U.S. Department of Housing and Urban Development (HUD), and 2005/2009 American Community Survey (ACS) data, provided by the U.S. Bureau of the Census, this article utilizes descriptive statistics and weighted least squares (WLS) regressions to analyze rates of seriously delinquent mortgages for Census tracts in all Metropolitan Statistical Areas (MSAs), differentiating among different Asian subgroups. Findings show that neighborhoods with Hmong, Laotian, and Cambodian households had relatively high rates of seriously delinquent mortgages, whereas neighborhoods with Chinese, Japanese, and Pakistani households had relatively low rates of seriously delinquent mortgages. - Reproduced.
Keywords: Foreclosure; Neighborhoods